Plasma Acylcarnitines and Amino Acid Levels As an Early Complex Biomarker of Propensity to High-Fat Diet-Induced Obesity in Mice - Horakova, Olga; Hansikova, Jana; Bardova, Kristina; Gardlo, Alzbeta; Rombaldova, Martina; Kuda, Ondrej; Rossmeisl, Martin; Kopecky, Jan (PloS one, 2016)
Obesity is associated with insulin resistance and impaired glucose tolerance, which represent characteristic features of the metabolic syndrome. Development of obesity is also linked to changes in fatty acid and amino acid metabolism observed in animal models of obesity as well as in humans. The aim of this study was to explore whether plasma metabolome, namely the levels of various acylcarnitines and amino acids, could serve as a biomarker of propensity to obesity and impaired glucose metabolism. Taking advantage of a high phenotypic variation in diet-induced obesity in C57BL/6J mice, 12-week-old male and female mice (n = 155) were fed a high-fat diet (lipids ~32 wt%) for a period of 10 weeks, while body weight gain (BWG) and changes in insulin sensitivity (ΔHOMA-IR) were assessed. Plasma samples were collected before (week 4) and after (week 22) high-fat feeding. Both univariate and multivariate statistical analyses were then used to examine the relationships between plasma metabolome and selected phenotypes including BWG and ΔHOMA-IR. Partial least squares-discrimination analysis was able to distinguish between animals selected either for their low or high BWG (or ΔHOMA-IR) in male but not female mice. Among the metabolites that differentiated male mice with low and high BWG, and which also belonged to the major discriminating metabolites when analyzed in plasma collected before and after high-fat feeding, were amino acids Tyr and Orn, as well as acylcarnitines C16-DC and C18:1-OH. In general, the separation of groups selected for their low or high ΔHOMA-IR was less evident and the outcomes of a corresponding multivariate analysis were much weaker than in case of BWG. Thus, our results document that plasma acylcarnitines and amino acids could serve as a gender-specific complex biomarker of propensity to obesity, however with a limited predictive value in case of the associated impairment of insulin sensitivity.
Keywords: obezita; Metabolome; Carnitine; Propensity Score; Insulin Resistance; Metabolomics; Diet, High-Fat; Female; analýza rozptylu; porucha glukózové tolerance; tendenční skóre; metabolomika; Analysis of Variance; Cluster Analysis; Phenotype; Biomarkers; zvířata; Blood Glucose; myši; Glucose Tolerance Test; aminokyseliny; Mice; Amino Acids; metabolom; glukózový toleranční test; Glucose Intolerance; biologické markery; ženské pohlaví; Male; karnitin; inzulinová rezistence; krevní glukóza; fenotyp; prognóza; shluková analýza; dieta s vysokým obsahem tuků; Obesity; Animals; mužské pohlaví; Disease Models, Animal; Prognosis; modely nemocí na zvířatech